OUTCOMES OF CORE DECOMPRESSION WITH PLATELET RICH PLASMA AND ORAL IBADRONATE SUPPLEMENTATION IN OSTEONECROSIS OF FEMORAL HEAD IN SICKLE CELL POSITIVE YOUNG ADULTS. - Dr Arvind Kumar; Dr Apurva Patel; Dr Sonal Lakum; Dr Mayank Gajera; Dr Harshil barot; Dr Aliasgar Rampurwala (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
BACKGROUND: Osteonecrosis of Femoral head (ONFH) is a common and serious complication of sickle cell disease (SCD). Without early treatment intervention, incidence of femoral head collapse and secondary osteoarthritis are very high and occur early in these patients. Aim of this study is to relief the symptoms, improve the functional outcomes for better activity of daily life (ADL) and delay the progression of head collapse. METHODS: In this retrospective study,40 hips in 30 pts were selected by inclusion and exclusion criteria. Mean age was 25 years. All selected cases were belonging to stage I, II and IIIa according to Modified Ficat and Arlet classification. In all pts core decompression were done by making two core tracks of 6 mm diameter with the help of Hollow-mill and PRP was injected in both core track and packed with bone wax. Oral Ibandronate given in all pts for 6 months. Percutaneous adductor tenotomy was performed in stage IIB and IIIa. Functional outcome were assessed by Modified Harris Hip Score (MHHS) and radiological assessment done by serial X-rays and MRI. Follow up were done up to 96 weeks. RESULTS: Average operative time was 30 minutes, average blood loss was 30 ml, average hospital stay was 7.5 days. Infection rate was only 5%. We observed 35% excellent, 45% good, 10% fair and 10% poor outcomes. CONCLUSION: We concluded that this technique is a relatively safe, cost effective, easy to perform, has very low complications rate and effective treatment option for the younger patients with ONFH in SCD